PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA OUTSOURCING YANG TIDAK MENERIMA JAMINAN SOSIAL TENAGA KERJA (CONTOH KASUS: PUTUSAN MAHKAMAH AGUNG NOMOR 1308 K/Pdt.Sus-PHI/2017) - evita liuswanto; Tundjung Herning Sitabuana (Fakultas Hukum Universitas Tarumanagara, 2021)
In accordance with the terms found in article 88 and article 99 of Act No. 13 of 2003 concerning Labour, employers are hired to give wages, the social security of the labor to their laborers. In reality many employers who do not comply with the requirement as do outsourcing workers who do not receive the right to receive the social security of labor when they are cut off. The question is how the law protects against outsourced workers who do not receive the social security of labor when they are cut off. To find the answer to that question, the author conducted a study using normative-law researched methods. In this descriptive study, secondary data is obtained through literature studies. After a qualitative analysis, the results indicate that the company as the employer has violated the requirements of labor laws because it does not provide labor security to outsourced labor workers. Thus began the company as the giver has violated preventive protections for outsourcing workers. Related to this the outsourcing of the labor force involved has been using repressive legal protection efforts by mediating through bipartite but failing. Therefore, the outsourcing work force filed a lawsuit with the industrial relations dispute settlement, but since it had also been a failure, the appeal to the Supreme Court was filed. Since the Supreme Court in its verdict also rejected the outsourcing action suit, it is recommended to use the extraordinary legal effort of reviewing new evidence (novum).